2015
DOI: 10.1161/circep.115.002956
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the Termination of Atrial Fibrillation by Localized Ablation

Abstract: Background Human atrial fibrillation (AF) can terminate after ablating localized regions, that supports the existence of localized rotors (spiral waves) or focal drivers. However, it is unclear why ablation near a spiral wave tip would terminate AF and not anchor reentry. We addressed this question by analyzing competing mechanisms for AF termination in numerical simulations, referenced to clinical observations. Methods and Results Spiral wave reentry was simulated in monodomain 2D myocyte sheets using clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…In the modern literature, the Fenton-Karma (FK) model (34,35) is widely used to simulate electrical activity in atrial tissue in more detail (35,36). To validate the applicability of our findings, the simulations with the FK model have been performed and are shown in SI Text.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the modern literature, the Fenton-Karma (FK) model (34,35) is widely used to simulate electrical activity in atrial tissue in more detail (35,36). To validate the applicability of our findings, the simulations with the FK model have been performed and are shown in SI Text.…”
Section: Discussionmentioning
confidence: 86%
“…S1-S3). It is shown that for the chosen parameter set of the FK model, the propagation block is achievable at the relatively strong inhomogeneity, which is, however, not unusual for cardiac tissue (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…While AF sources have been questioned, those studies had issues such as atrial cycle lengths of 250–500ms (dominant frequencies 2–4 Hz) in many patients ostensibly with AF and analysis of unipolar signals using indices designed for bipolar signals (Shannon's entropy) 19 , or mapped very small areas 8 . Recent data showing how localized ablation can terminate AF rotors, by interacting with non-uniformities in remodeled atria, explain and thus strengthen the results of AF source ablation 20 . At the other end of the spectrum, it has been proposed that debulking should be further extended – such as by posterior LA wall ablation.…”
Section: Introductionmentioning
confidence: 74%
“…This model is now supported by wide evidence in many patients ranging from optical mapping of human AF, 7 multicenter (non-randomized) clinical trials of AF rotor ablation, [8][9][10][11][12][13] optical mapping of animal AF, 14 and mathematical analyses. 15 Moreover, this model can reconcile the paradox that limited ablation can terminate persistent AF in some patients, 8,16,17 while extensive (untargeted) ablation of left atrial regions can be ineffective in others. 1,2,18 The source model may contradict the multiwavelet hypothesis, in which AF is caused by disordered waves alone, 19,20 although ongoing studies on the interaction between organized sources and disordered waves may reconcile this.…”
Section: Introductionmentioning
confidence: 96%